Association of anaemia and all‐cause mortality in patients with ischaemic heart failure varies by renal function status. (10th April 2021) - Cai, Anping; Wu, Zejia; Xu, Lan; Xia, Shuang; He, Xuyu; Zhang, Ying; Chen, Jiyan; Zhou, Yingling; Li, Liwen
Abstract: Aims: The aims of the current study were to evaluate the association between anaemia and all‐cause mortality according to chronic kidney disease (CKD) status and to explore at what level of haemoglobin concentration would the all‐cause mortality risk increase prominently among CKD and non‐CKD patients, respectively. Methods and results: This is a prospective cohort study, and 1559 patients with ischaemic heart failure (IHF) were included (mean age of 63.5 ± 11.0 years, 85.8% men) from December 2015 to June 2019. Patients were divided into the CKD ( n = 481) and non‐CKD ( n = 1078) groups based on the estimated glomerular filtration rate of 60 mL/min/1.73 m 2 . In the CKD group, the incidence rate of all‐cause mortality in anaemic and non‐anaemic patients was 15.4 per 100 person‐years and 10.8 per 100 person‐years, respectively, with an incidence rate ratio of 1.42 (95% confidence interval: 1.00–2.02; P ‐value = 0.05). In the non‐CKD group, the incidence rate of all‐cause mortality in anaemic and non‐anaemic patients was 9.8 per 100 person‐years and 5.5 per 100 person‐years, respectively, with an incidence rate ratio of 1.78 (95% confidence interval: 1.20–2.59; P ‐value = 0.005). After a median follow‐up of 2.1 years, the cumulative incidence rate of all‐cause mortality in anaemic and non‐anaemic patients was 41.5% and 44.1% ( P ‐value = 0.05) in the CKD group, and 30.9% and 18.1% ( P ‐value < 0.0001) in the non‐CKD group. In the CKD group, cumulative incidence rate of all‐cause mortality increased prominently when haemoglobin concentration was below 100 g/L, which was not observed in the non‐CKD group. Conclusions: Results of the current study indicated that among IHF patients, the association between anaemia and all‐cause mortality differed by the renal function status. These findings underline the importance to assess mortality risk and manage anaemia among IHF patients according to the renal function status.